Awareness and knowledge of glaucoma among the patients attending a tertiary eye hospital with and without glaucoma diagnosis - Sultana, Habiba; Islam, Khairul; Huq, M. Sajidul (International Journal of Advances in Medicine, 2024)
Background: Glaucoma, a leading cause of irreversible blindness, remains under-recognized in many regions, including Bangladesh. This study aimed to assess the awareness and knowledge of glaucoma among the patients attending a tertiary eye hospital with and without glaucoma diagnosis. Methods: This cross-sectional study was conducted on 300 individuals attending deep eye care foundation, Rangpur, from April 2023 to September 2023. Informed consent was obtained from eligible participants over 18 years. The questionnaire, available in both English and Bengali, collected demographic data and included questions on glaucoma awareness and knowledge. Data were analysed using SPSS 25, and the chi-square test was applied to determine statistical significance. Results: Among the participants, 34.7% had heard of glaucoma, with doctors/hospitals being the primary source of information. Awareness varied significantly based on age, residency, education, occupation, and income levels. Among those aware of glaucoma, 59.6% had poor knowledge, 33.7% had average knowledge, and only 6.7% had good knowledge. No significant association was found between glaucoma patients and non-glaucoma patients regarding knowledge level. Conclusions: This study revealed a substantial gap in glaucoma awareness and knowledge in Bangladesh. While a notable portion of the population had heard of glaucoma, their understanding of the condition was limited, emphasizing the need for targeted awareness campaigns and improved access to eye care services. Addressing these gaps is crucial for early diagnosis, treatment, and preventing irreversible blindness while reducing the economic burden associated with glaucoma-related healthcare costs.